Coping With Violence: A Comprehensive Framework and Implications for Understanding Resilience. (July 2013) - Boxer, Paul; Sloan-Power, Elizabeth
Interpersonal violence is present at all levels of influence in the social ecology and can have comprehensive and devastating effects on child and adolescent development through multiple simultaneous channels of exposure. Children's experiences with violence have been linked with a range of behavioral and mental health difficulties including posttraumatic stress disorder and aggressive behavior. In this article, we offer a conceptual framework delineating the ways in which children and adolescents might encounter violence, and a theoretical integration describing how violence might impact mental and behavioral health outcomes through short- and long-term processes. We propose that coping reactions are fundamental to the enduring effects of violence exposure on their psychosocial development and functioning. Finally, we discuss the manner in which coping efforts can support resilience among children exposed to violence and suggest new directions for research and preventive intervention aimed at optimizing outcomes for children at risk of exposure.